2009
DOI: 10.1007/s00383-009-2468-x
|View full text |Cite
|
Sign up to set email alerts
|

Ciliated hepatic foregut cysts in children

Abstract: Ciliated hepatic foregut cyst (CHFC) is a rare foregut developmental malformation usually diagnosed in adulthood; however, rare cases have been reported in the pediatric population. CHFC can transform into a squamous cell carcinoma resulting in death despite surgical resection of the isolated malignancy. We report the presentation, evaluation, and surgical management of a symptomatic 17-year-old girl found to have a 6.5 × 4.5 centimeter CHFC and suggest that all patients with suspected CHFC undergo prompt eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 13 publications
0
21
0
8
Order By: Relevance
“…This cyst did not have cartilage but did have abundant mucous secreting glands and a ciliated epithelium. Other studies described mucous filled cysts lined with ciliated cells in the liver of infant [10][11][12], while others noted similar cysts in the retroperitoneum. To our knowledge, this is the first case report describing an intraabdominal bronchogenic cyst of the small bowel mesentery in the pediatric population.…”
Section: Discussionmentioning
confidence: 94%
“…This cyst did not have cartilage but did have abundant mucous secreting glands and a ciliated epithelium. Other studies described mucous filled cysts lined with ciliated cells in the liver of infant [10][11][12], while others noted similar cysts in the retroperitoneum. To our knowledge, this is the first case report describing an intraabdominal bronchogenic cyst of the small bowel mesentery in the pediatric population.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, our review of all pediatric cases revealed that approximately two thirds of the cysts in children were multilocular [2][3][4][5][6][7]11,13,15]. Three of our pediatric CHFCs were also multilocular.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive tumor behavior of SCC is demonstrated by the deaths of 2 of these patients within 2 and 9 months of tumor excision [2,11]. Previously, observation or aspiration of cysts has been recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Ele apresenta como característica típica a presença de quatro camadas da parede do cisto, distintas a microscopia. 8,9,10,11,12 A despeito de sua raridade, o CCH está aumentando em incidência. Este é sem dúvida devido ao aumento do uso de métodos de imagem radiológica não invasivos nos últimos 20 anos, acessibilidade e surgimento de novas técnicas de exames.…”
Section: Introductionunclassified